2000
DOI: 10.1164/ajrccm.161.1.9810007
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Two Death Pathways of Perforin/Granzyme and FasL/Fas in Septic Acute Respiratory Distress Syndrome

Abstract: Accumulation and activation of inflammatory cells in the lung characterize the acute respiratory distress syndrome (ARDS). However, the precise mechanism for lung epithelial and endothelial cell damage remains unknown. Based on evidence that rapid apoptosis caused by CD8(+) cytolytic T cells can induce pathological cell death, we hypothesized that this mechanism may also participate in the acute lung injury, and attempted to evaluate apoptosis-related factors in bronchoalveolar lavage fluid (BALF) from ARDS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
93
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 26 publications
6
93
0
3
Order By: Relevance
“…41 These investigators have also shown high levels of mRNA for several products of CD8 ϩ T cells, including granzymes A and B, perforin, Fas, and Fas ligand in the bronchoalveolar fluid of patients during the acute phase of lung injury. 42 These molecules participate in apoptotic cytotoxicity induced by CD8 cells and could contribute to lung injury. The large accumulation of granulocytes occurs in numerous types in acute lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…41 These investigators have also shown high levels of mRNA for several products of CD8 ϩ T cells, including granzymes A and B, perforin, Fas, and Fas ligand in the bronchoalveolar fluid of patients during the acute phase of lung injury. 42 These molecules participate in apoptotic cytotoxicity induced by CD8 cells and could contribute to lung injury. The large accumulation of granulocytes occurs in numerous types in acute lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute phase (within 24 h of diagnosis) of septic ARDS patients, expression of perforin and granzyme B on lymphocytes and the presence of high levels of soluble CD95 ligand (CD95L) in the bronchoalveolar lavage fluid (BALF) have been detected. These findings are absent in late phase or septic non-ARDS patients [16]. Such reports suggest the participation of CD95/CD95L-and perforin/ granzyme-mediated pathways in lung epithelial cell injury in ARDS and interstitial pneumonia.…”
Section: Introductionmentioning
confidence: 85%
“…The epithelial hypothesis suggests that the epithelial injury that occurs during ALI is associated with apoptotic death of alveolar epithelial cells and predicts that anti-apoptotic therapeutic agents may be beneficial in preventing or treating ALI [13,34,35]. Our results showed that caspase-3 activity was increased in lung tissue following challenge with OA.…”
Section: Discussionmentioning
confidence: 52%